Self‐Powered Drug‐Delivery Systems Based on Triboelectric Nanogenerator - Zhirong Liu; Linlin Li (Advanced Energy & Sustainability Research, 2021)
Triboelectric nanogenerator (TENG) can convert mechanical energy into electricity via the coupling of triboelectrification and electrostatic induction. Due to its advantages of flexible, lightweight, high‐energy conversion efficiency and shape‐adaptive ability, implantable and wearable TENG have shown great potentials in biomedical field for biomechanical energy harvesting, biosensing, and therapy. In this Perspective, recent advances of TENG for self‐powered drug delivery, mainly including controlled drug release as well as drug delivery based on electroporation and iontophoresis are systematically overviewed. Also the significance of self‐powered drug‐delivery system in personalized healthcare is emphasized, and conclude with the open challenges and future perspectives of TENG‐based drug‐delivery systems.